Antioxidative and Anti-Inflammatory Activity of Ascorbic Acid - Agnieszka Gęgotek; Elżbieta Skrzydlewska (MDPI AG, 2022)
Ascorbic acid, as a one of the basic exogenous vitamins, occurs in the body in the form of ascorbate, known for its strong antioxidant and anti-inflammatory properties. The presented review shows not only the importance of ascorbate as a free radical scavenger but also summarizes its antioxidant action based on other mechanisms, including the activation of intracellular antioxidant systems and its effect on the NFκB/TNFα pathway and apoptosis. Ascorbate interacts with small-molecule antioxidants, including tocopherol, glutathione, and thioredoxin; it can also stimulate biosynthesis and the activation of antioxidant enzymes, such as superoxide dismutase, catalase, or glutathione peroxidase. Moreover, ascorbate promotes the activity of transcription factors (Nrf2, Ref-1, AP-1), which enables the expression of genes encoding antioxidant proteins. Additionally, it supports the action of other exogenous antioxidants, mainly polyphenols. In this regard, both DNA, proteins, and lipids are protected against oxidation, leading to an inflammatory reaction and even cell death. Although ascorbate has strong antioxidant properties, it can also have pro-oxidant effects in the presence of free transition metals. However, its role in the prevention of DNA mutation, inflammation, and cell apoptosis, especially in relation to cancer cells, is controversial.